If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1x = 4 + -5 Combine like terms: 2x + -1x = 1x 1x = 4 + -5 Combine like terms: 4 + -5 = -1 1x = -1 Solving 1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = -1 Simplifying x = -1
| 2ln(x-2)=4 | | 4yd=144in | | 3x(21-x)=x(3x-2)-24 | | x*(x+4)=96 | | 2s^2-9s=0 | | 3x-3=-11-5x | | 6y+3x+5y-x= | | 4sin^2x=2 | | x*x+4=96 | | 6x+3=2x+4 | | (4x-16)(x+4)= | | x(x+5)=x^2-15 | | 7x+4=2x+1 | | 13+n=18 | | 9x^2-3x+12=0 | | K=nob | | 3(x+5)-7=15-3x-7+6x | | 6a-27=9 | | 3p+4-p-3= | | -3+7(x-2)=16x+3-9x | | (8s-3)-4(8-12s)=2.75 | | 4(x+5)-2= | | (8s-3)-4(8-12s)=0 | | 24x^4=0 | | 6(a-7)+16=4(a-6) | | 3(x-5)=41-4x | | 7(x-5)=-21 | | x^3=730 | | 4x-6=2x+34 | | 3x-1.2=2.4 | | x^3-6x^2-4=0 | | c+5d+4c-2d= |